2021
DOI: 10.24271/garmian.207017
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Management Information System in Improving Organizational Performance and Effectiveness

Abstract: The main purpose of this study was to show the role of management information system application in improving the performance of the public universities in Sulaimani city of Iraq. The study's sample consists of (200) of administrative employees from all the public universities in the city. The most important conclusion of the research is that all predicted variables of (System and Information Quality, Customer Satisfaction, User Training, Organizational Leadership, and Organization Services Quality) are signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…As Obednikovska, et al (2019) highlighted internet communication for businesses is based on the application of several tools, such as websites, databases, systems, and social media platforms. You can increase Internet commerce through While technology has occupied the world and the market, managers were forced to adapt to these new methods and challenges to not lose the market and survive their businesses, technology made managers think of doing things differently by trying to understand their customers' needs and apply this while planning their management strategy, the results of this research showed that using technology for management improves the customer satisfaction (Fadhil, et al, 2020). Electronic marketing refers to the planning and based on marketing activities that are part of the marketing mix to meet the needs of the intended consumers' desires, and also achieve the company's objectives, using either traditional marketing techniques or the Internet.…”
Section: Introductionmentioning
confidence: 90%
“…As Obednikovska, et al (2019) highlighted internet communication for businesses is based on the application of several tools, such as websites, databases, systems, and social media platforms. You can increase Internet commerce through While technology has occupied the world and the market, managers were forced to adapt to these new methods and challenges to not lose the market and survive their businesses, technology made managers think of doing things differently by trying to understand their customers' needs and apply this while planning their management strategy, the results of this research showed that using technology for management improves the customer satisfaction (Fadhil, et al, 2020). Electronic marketing refers to the planning and based on marketing activities that are part of the marketing mix to meet the needs of the intended consumers' desires, and also achieve the company's objectives, using either traditional marketing techniques or the Internet.…”
Section: Introductionmentioning
confidence: 90%
“…A Management Information System (MIS) is a system that has been specifically designed to gather, oversee, store, analyse, and furnish pertinent and precise information to leaders, managers, and decision-makers within an organisation. The primary objective of a management information system is to support management in the efficient and effective management of both operational and strategic aspects of the organisation (Fadhil et al, 2021). Key components of a Management Information System encompass: 1.…”
Section: Literature Review Management Information Systemmentioning
confidence: 99%
“…It requires the conveyance and transportation framework to adopt information management models to eliminate functional errors, optimize vehicular movement and distribution routes (Kazuhiro, Yusuke and Yoichi, 2022). This condition favours the utilization of external logistics providers as accomplices in logistics operations, seeking a more productive service to the end client at a lower cost utilizing an information management framework (Fadhil, Mahmod and Ahmed, 2021). The echelon of information management is expanding, zeroing in on digital platforms such as social handles, intranet/internet, adding more pressures on logistics operations performance.…”
Section: Introductionmentioning
confidence: 99%